Caloneis nanyiensis sp. nov. (Bacillariophyta) from Nanyi Lake of Anhui Province, China - Yong Fang; Pan Yu; Qing-Min You; John Patrick Kociolek; Yue Cao; Quan-Xi Wang; Zhi-Ping Qian (PhytoKeys)
A new species, Caloneis nanyiensis sp. nov., is described from Nanyi Lake, the largest lake in southern Anhui Province, China. Observations were made using a light and scanning electron microscope documenting the size, shape and ultrastructure of the new species. Caloneis nanyiensis sp. nov. has rhombic valves with acutely rounded apices. The raphe is narrow and arched. An internal axial plate covers the alveoli, leaving small marginal openings bordered by costa, thickened and raised from the valve face. The striae are slightly radiate to parallel in the central area, becoming radiate towards the apices. By comparing the new species with similar Caloneis species, C. nanyiensis sp. nov. was confirmed to be sufficiently different with respect to valve size and striae density to be recognised as new to science. The new species lives in freshwater habitats and epiphytic on Cladophora. The discovery enhances our knowledge of the diversity of freshwater diatoms in China.